Hb F Levels in β-Thalassemia Carriers and Normal Individuals: Known and Unknown Quantitative Trait Loci in the β-Globin Gene Cluster. (4th May 2022) - Manco, Licínio; Santos, Raquel; Rocha, Catarina; Relvas, Luís; Bento, Celeste; Maia, Tabita; Gomes, Verónica; Amorim, António; Prata, Maria J.
Abstract: In the already identified quantitative trait loci (QTL), modulating Hb F levels are cis -acting haplotypes of the β-globin gene cluster itself, although the single nucleotide polymorphisms (SNPs) accounting more for the association, remain uncertain. In this study, the role in Hb F production of previously reported candidate SNPs within the β-globin gene cluster was reexamined, along with a yet poorly studied variation in the BGLT3 gene. In a sample of β-thalassemia (β-thal) carriers, we succeeded in replicating the significant association between increased Hb F levels and rs7482144 (C>T) ( HBG2 Xmn I), which is the most well-established variation in the cluster influencing the trait. This SNP was found to be in strong linkage disequilibrium (LD) with a variation in the HBBP1 gene [rs10128556 (G>A)], which consistently revealed a similar association signal. Remarkably, much stronger than the latter associations were those involving both rs968857 (T allele) (3' HBBP1 ) and rs7924684 (G allele) ( BGLT3 ), two SNPs that were also in strong LD. As the pattern of LD detected in the β-globin gene cluster does not correlate with a tight linkage between markers, complex interactions between SNPs at the cluster seem to modulate Hb F. Seeing that no such associations were detected in normal subjects, the question can be raised on whether, under erythropoiesis stress, epigenetic mechanisms contribute to change the regulation of the entire β-globin gene cluster. In conclusion, we provide statistical evidence for a new player within the β-globin gene cluster, BGLT3, that in cooperation with other regions influences Hb F levels in β-thal carriers.